How technology affected our privacy - Sehnaz, Ahmetoglu; Zeki, Akram M. (International Journal of Science and Research, 2015)
After the recent spread of the Internet, many technology terms appeared like Smartphone, social media and cloud computing. Flexibility in use this technology encourage people to communicate and share their information in all kinds: photos, videos, documents and sometimes sensitive information like bank account. Annually we note the increased number of users of this technology to be arrived over billions of users. Most of these users are public which they do not realize ambiguity of technology and therefore easier to access their information. The abundance of information and poor knowledge of users about privacy led to the emergence of numerous threats and fears under this term. Thus, the importance of educating people about privacy issues and related risk factors become essential. This paper views the definition of privacy and what level of awareness should be applied. With try to understand some security issues and related laws. And compare between two different privacy laws.